2013
DOI: 10.1021/jz4014085
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Mesoporous Composites as Molecular Sieves for SERS Detection

Abstract: Application of surface-enhanced Raman scattering (SERS) spectroscopy to the ultrasensitive analysis of small molecules in biological samples is complicated by signal contamination by ubiquitous macromolecules such as proteins, nucleic acids, or lipids. We present a proof-of-concept study of the application of composite films comprising branched gold nanoparticles embedded in mesoporous thin films, which act as molecular sieves. The inorganic mesoporous layer only allows the diffusion of small molecules towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 39 publications
(73 reference statements)
3
89
0
Order By: Relevance
“…Thus, this system does not seem useful for analytical applications, in agreement with previously reported results. 34 Finally, no significant differences were observed between those systems built with 35 and 66 nm NPs, when minimum acquisition time was used as the comparative parameter.…”
Section: >120mentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, this system does not seem useful for analytical applications, in agreement with previously reported results. 34 Finally, no significant differences were observed between those systems built with 35 and 66 nm NPs, when minimum acquisition time was used as the comparative parameter.…”
Section: >120mentioning
confidence: 93%
“…For architecture (1), Au NPs and TiO 2 thin films have been used. 12,[34][35] For architecture (2), combinations of Ag NPs and different mesoporous films (TiO 2 , SiO 2 and ZrO 2 ) have been reported. [36][37] The main features regarding SERS activity and applications of each of these architectures have been presented, though separately and using different measurement conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To our purposes, the most important quantum size effect is the surface plasmon resonance (SPR) providing light absorption in the visible range by the red shift of the Drude frequency (in the UV range for metals) to the optical region provoked by the modification of the selection rules for polarization induced by the surface electrons. In fact, a plasmon is nothing but a quantized in-phase collective oscillation of polarized "free" conduction electrons confined within a metal/dielectric boundary [14,15]. The optical properties of plasmonic nanoparticles can hardly be explained employing traditional theories (as those based in the dipole approximation [16]), but a size dependence is foreseen (and experimentally demonstrated) as a consequence of the differential contributions of the interband transitions (due to d electrons) and Drude parts of the dielectric function, which causes that surficial scattering exceeds that one coming from the bulk [17].…”
Section: Introductionmentioning
confidence: 99%
“…These concerns can be addressed by incorporating mesoporous inorganic thin films into the structure of the plasmonic substrate. Interestingly, the mesoporous nature of the films can also be used to direct anisotropic nanoparticle growth within the films, and more importantly, that the mesoporous films act as molecular sieves to let small molecules such as quorum sensing signals pass through the film, while larger biomolecules such as proteins are unable to enter [65]. One promising approach for biological studies of bacterial growth on topographically patterned substrates has been reported by Hamon and coworkers, using sol-gel silica growth on gold nanorod supercrystal micropatterns (Figure 5e) [66].…”
Section: Concept: Sers Detection Of Quorum Sensing For Early Stage Momentioning
confidence: 99%